Development of High-Resolution Proton Transfer Reaction Time-of-Flight Mass Spectrometer and its Application in Continuous Fixed-Point Monitoring of Atmospheric VOCs - Zhong-jun ZHAO; Han-lu YUE; Xing GUO; Fu-long DENG; Xing-liang HE; Cheng-lin LI; Yun-hai XU; Yan-ting YANG; Yi-xiang DUAN (Zhipu Xuebao)
The online mass spectrometry for volatile organic compounds (VOCs) analysis has rapidly advanced and found extensive applications in environmental monitoring, food safety, and life science research due to its fast analysis speed, high temporal resolution, high sensitivity, and simplified spectrum interpretation. This kind of online mass spectrometry fills the gap in high-throughput online detection applications where gas chromatography-mass spectrometry (GC-MS) falls short. The qualitative capabilities of online mass spectrometry rely on accurate measurement and resolution of the mass peaks, thus enhancing the mass resolution is a crucial direction for the development of such instruments. This study reported the development of a high-resolution proton transfer reaction time-of-flight mass spectrometer (PTR-TOF MS 6000) and its exploratory applications in accurately identifying compounds with the same nominal mass but different molecular weights, as well as in real-time monitoring of the atmospheric VOCs. This instrument utilized a hydrated ion molecule-ion reactor as an efficient ionization source, achieving soft ionization with the limit of detection below 0.005 nmol/mol for various VOCs, and sensitivity reaching thousands of counts per nmol/mol. The low vacuum part of the ion transmission system used a radio frequency quadrupole as an ion-guiding device to ensure ion transmission efficiency. The mass-to-charge ratio measurement of ions was performed using a high-resolution time-of-flight mass analyzer, achieving a resolution greater than 6205 full width at half maximum (FWHM) at the molecular ion peak of toluene (m/z 93.070, [M+H]+). The developed high-resolution PTR-TOF MS 6000 can effectively distinguish VOCs with the same nominal mass, such as crotonaldehyde ([M+H]+, m/z 71.049) and 1-pentene ([M+H]+, m/z 71.086), thereby enhancing the qualitative accuracy of online VOCs analysis without chromatographic separation and providing more accurate and valuable information for practical applications. In preliminary exploratory experiments for atmospheric VOCs monitoring, PTR-TOF MS 6000 was used to monitor real-time concentration changes of VOCs, such as benzene, toluene, and xylene in the atmospheric environment. This instrument successfully detects and accurately quantifies multiple substances with the same nominal molecular weight but different mass-to-charge ratios, such as furan and isoprene, without the need for complex preprocessing, due to enhanced qualitative capabilities. Our work fulfills the need for real-time tracking of VOCs variations and provides a more accurate solution for continuous monitoring of atmospheric VOCs, extending application field of the PTR-TOF MS.